Prolonged survival of venereal Tritrichomonas foetus parasite in the gastrointestinal tract, bovine fecal extract, and water - Martínez, Cristian I. (2023)
Bovine tritrichomonosis is a venereal disease that causes economic losses around the world. Over the last 100 years, the life cycle of the protozoan Tritrichomonas foetus in bovines has only considered venereal transmission, almost exclusively through natural mating from an infected animal to a healthy animal. Here, we provide the first direct evidence that T. foetus can survive the passage through the gastrointestinal tract in bovines. We demonstrated that the parasite can be discharged by feces in orally infected animals and contaminate the cow’s reproductive tract. We showed that the parasite is capable of surviving at pH conditions usually found along the bovine gastrointestinal tract, and our findings suggest that the parasites could survive in bovine feces and water for several days, probably through the formation of resistant pseudocysts or cyst-like structures. Taken together, our results demonstrate that T. foetus is more resistant to adverse external conditions than previously considered, which could be relevant for the life cycle of this parasite in bovines.